The Interaction of Morphological and Stereotypical Gender Information in Russian - Garnham, Alan; Yakovlev, Yuri (Frontiers in Psychology, 2015)
Previous research, for example in English, French, German, and Spanish, has investigated the interplay between grammatical gender information and stereotype gender information (e.g. that secretaries are usually female, in many cultures), in the interpretation of both singular noun phrases (the secretary) and plural nouns phrases, particularly so-called generic masculines – noun that have masculine grammatical gender but that should be able to refer to both groups of men and mixed groups of men and women. Since the studies have been conducted in cultures with broadly similar stereotypes, the effects generally reflect differences in the grammatical systems of the languages. Russian has a more complex grammatical gender system than the languages previously studied, and, unlike those languages frequently presents examples in which grammatical gender is marked on the predicate (in an inflection on the verb). In this study we collected stereotype norms for 160 role names in Russian, providing a useful resource for further work in this language. We also conducted a reading time study examining the interaction of grammatical and stereotype gender information in the interpretation of both Russian singular noun phrases, and plurals that were (potentially) generic masculines. Our results show that, although both types of gender information are used, as available, the effects of grammatical marking on the predicate are not as strong as those.